Cassie's word quilt - Ringgold, Faith (New York : Knopf : Distributed by Random House, 2002)
Names the people and objects that make a girl's New York City apartment, school, and neighborhood special.
Keywords: African Americans -- Fiction; Vocabulary; Picture books; Harlem (New York, N.Y.) -- Fiction